Cultural Policy and Industries of Identity Québec, Scotland, & Catalonia - Beauregard, Devin (Springer International Publishing, 2018)
This book explores the cultural policies of sub-states with strong nationalist inclinations-in particular, Québec, Scotland, and Catalonia-and their trend, in recent years, towards promoting and supporting the cultural industries as a means of not just preserving their respective cultural identities, but of growing them. This represents a paradigm shift from the traditional discourse around cultural policy, which often posits that concepts of identity fall under the purview of heritage institutions and organizations, not that of industries. Drawing on the work of Boltanski and Thévenot-notably, their economies of worth framework-this book develops a typological analysis of cultural policy. Specifically, this book seeks to fill a gap in the cultural policy and cultural studies literature where identity and the cultural industries are concerned, expanding on the role of the cultural industries in the development of identity and the implications it has for cultural policy. .